The secret of my success [videorecording (DVD)] - Carothers, A. J. (Universal, 1998)
In this lampoon of corporate business life, a kid from Kansas (Michael J. Fox) comes to New York, conquers the business world and maneuvers his way from the mailroom to the boardroom in a matter of weeks.